Understanding the new BRD4‐related syndrome: Clinical and genomic delineation with an international cohort study. Issue 2 (25th April 2022) - Jouret, Guillaume; Heide, Solveig; Sorlin, Arthur; Faivre, Laurence; Chantot‐Bastaraud, Sandra; Beneteau, Claire; Denis‐Musquer, Marie; Turnpenny, Peter D.; Coutton, Charles; Vieville, Gaëlle; Thevenon, Julien; Larson, Austin; et al.
Abstract: BRD4 is part of a multiprotein complex involved in loading the cohesin complex onto DNA, a fundamental process required for cohesin‐mediated loop extrusion and formation of Topologically Associating Domains. Pathogenic variations in this complex have been associated with a growing number of syndromes, collectively known as cohesinopathies, the most classic being Cornelia de Lange syndrome. However, no cohort study has been conducted to delineate the clinical and molecular spectrum of BRD4 ‐related disorder. We formed an international collaborative study, and collected 14 new patients, including two fetuses. We performed phenotype and genotype analysis, integrated prenatal findings from fetopathological examinations, phenotypes of pediatric patients and adults. We report the first cohort of patients with BRD4 ‐related disorder and delineate the dysmorphic features at different ages. This work extends the phenotypic spectrum of cohesinopathies and characterize a new clinically relevant and recognizable pattern, distinguishable from the other cohesinopathies. Abstract : This work presents the first cohort of patients with the newly described BRD4 ‐related disorder through a collection of 14 cases, broadening the phenotype with particular emphasis on a new clinically relevant and recognizable core pattern, distinguishable from the other cohesinopathies and especially different from the Classic CdLS phenotype.